2010
DOI: 10.1523/jneurosci.6284-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Rhythmic GABAergic Septal Activity and Memory-Associated θ Oscillations after Hippocampal Amyloid-β Pathology in the Rat

Abstract: The memory deficits associated with Alzheimer's disease result to a great extent from hippocampal network dysfunction. The coordination of this network relies on theta () oscillations generated in the medial septum. Here, we investigated in rats the impact of hippocampal amyloid ␤ (A␤) injections on the physiological and cognitive functions that depend on the septohippocampal system. Hippocampal A␤ injections progressively impaired behavioral performances, the associated hippocampal power, and frequency respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 91 publications
7
81
0
1
Order By: Relevance
“…Although in this work, we only focus on the system dynamical changes caused by the pathological changes in the hippocampal pyramidal neurons, it should be admitted that the Aβ-indued hippocampal dysfunction may be more complex. For example, it has been shown in (Villette et al 2010;Colom et al 2010) that Aβ-induced GABAergic and cholinergic system degeneration in the medial septum may also cause hippocampal dysfunctions. GABAergic neurons inhibit hippocampal OLM and basket neurons and act as a hippocampal theta rhythm pacemaker and cholinergic neurons control the acetylcholine level in the hippocampus, which can change the dynamics of pyramidal neurons and synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Although in this work, we only focus on the system dynamical changes caused by the pathological changes in the hippocampal pyramidal neurons, it should be admitted that the Aβ-indued hippocampal dysfunction may be more complex. For example, it has been shown in (Villette et al 2010;Colom et al 2010) that Aβ-induced GABAergic and cholinergic system degeneration in the medial septum may also cause hippocampal dysfunctions. GABAergic neurons inhibit hippocampal OLM and basket neurons and act as a hippocampal theta rhythm pacemaker and cholinergic neurons control the acetylcholine level in the hippocampus, which can change the dynamics of pyramidal neurons and synapses.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, impairment of hippocampal theta oscillation was considered to underlie compromised hippocampal-dependent cognitive function in APP/PS1 mice (Howlett et al, 2004;Villette et al, 2010). Therefore, we studied the efficacy…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…A decreased neocortical inhibition in an AD model has been reported by Busche et al (2008), who found that near amyloid plaques neurons are hyperactive, probably because of a less efficient inhibition by GABAergic neurons. Moreover, it has been recently shown that rhythmic bursting neurons of the medial septum, which are necessary for hippocampal theta rhythm and learning and are fast spiking neurons expressing Kv3.1 (Henderson et al 2010), fire at lower rates after injection of betaamyloid (Villette et al 2010). Therefore, it can be hypothesised that the reduction of Kv3.1 expression could modify Kv3 current density and channel stoichiometry and thereby play a role in the impairment of inhibition in neocortical networks in AD.…”
Section: Kv3 Expression In Appps1 Micementioning
confidence: 99%